Study on the dynamic response and the hazard of rock burst under the influence of fault slip - Kong, Peng; Liu, Rong; Xing, Luyi; Li, Zhihong; Xu, Chuanwei; Zhang, Zhongteng (Frontiers in Earth Science, 2023)
In the process of coal mine production, rock burst accidents near faults occur frequently. In order to further reveal the induced mechanism of fault slip rock burst, a numerical simulation method for dynamic calculation of fault slip under the influence of mining is proposed, and the law of fault slip and dynamic response characteristics of the stope are studied. The study shows that with the working face getting closer to the fault, the fault activity and the number of high-energy microseismic events increase significantly, and the fault slip dynamic load has a significant impact on the vibration velocity and abutment stress of coal and rock mass near the stope. Under the effect of a strong fault slip dynamic load, the coal and rock mass in the area with peak abutment stress undergo plastic failure and release a large amount of energy, and the potential of fault slip rock burst is high. The evaluation index Icd of rock burst hazard under fault slip dynamic load is proposed, and the rock burst hazard of working face passing through the fault is analyzed. The research results provide a theoretical basis for further revealing the induced mechanism and hazard assessment of fault slip rock bursts.